Advantages of nanoscale bioactive glass as inorganic filler in alginate hydrogels for drug delivery and biofabrication. Issue 1 (31st December 2022) - Bider, Faina; Karakaya, Emine; Mohn, Dirk; , Aldo R.; Boccaccini,
Abstract: Sodium alginate is a natural biocompatible polymer obtained from brown algae which has found numerous biomedical applications. Inorganic fillers, such as nanosized bioactive glass (nBG) particles, are well known for their outstanding properties in terms of being osteoconductive and osteoinductive and therefore finding application in bone tissue engineering. In this study, the impact of nBG particles on alginate hydrogels was investigated for applications of the composite hydrogel in biofabrication and drug delivery. The influence of nBG particles on properties such as printability, drug release ability and bioactivity (capability to form a hydroxyapatite (HAp) layer on the surface of nBG-alginate capsules) was studied. In vitro cell studies proved high cell viability of all inks. Due to the presence of nBG particles, more precise printed grids and pore sizes were achieved. Moreover, a decrease of the release of the model drug icariin in the presence of nBG particles was determined. The formation of a HAp layer on the surface of nBG-alginate capsules was assessed by FTIR, XRD and SEM. Overall, the addition of nBG particles into alginate hydrogels led to the improvement of the relevant properties investigated. Therefore, nBG-alginate systems should gain more attention for 3 D bioprinting and drug delivery approaches. Supplemental data for this article is available online at https://doi.org/10.1080/26889277.2022.2039078 .